Answer:
g(f(x)) = 1x² + 1
Step-by-step explanation:
We are given:
f(x) = x² - 1
g(x) = x + 2
And we want to find g(f(x)).
To do this, we substitute f(x) as x in x+2 (the expression that is equal to g(x)), as g(f(x)) is saying that f(x) is the value of x in g(x).
So, this will be:
g(f(x)) = x² - 1 + 2
Simplify
g(f(x)) = x² + 1
In your system, place 1 in front of x² - this is the coefficient of x², and also 1 after that - this is a constant.
Answer:
It would quadruple it.
Step-by-step explanation:
When you divide by a fraction you first flip it then you multiply straight across. For example 3 / (1/4) you flip then multiply which gives you 3/1 * 4/1 = 12/1 which simplifies to 12
1) £20
2) 18/4 * 7 = 31,5msquared
3) X= (3-1)/5 = 2/5 = 0.4
4) A(n) = 2 + 5n
5) t(3) = 6*3 + 2 = 20
AL=5ah!!!!!!!!!! Hope it helps
Answer:
25,328.941 ÷ 104= 7.90415302
Step-by-step explanation: